Isolated CyaA-RTX subdomain from Bordetella pertussis: Structural and functional implications for its interaction with target erythrocyte membranes - Riyaz Ahmad Pandit (2018)
© 2015 Elsevier Inc. The 126-kDa Bordetella pertussis CyaA-hemolysin (CyaA-Hly) was previously expressed in Escherichia coli as a soluble precursor that can be acylated to retain hemolytic activity. Here, we investigated structural and functional characteristics of a ∼100-kDa isolated RTX (Repeat-in-ToXin) subdomain (CyaA-RTX) of CyaA-Hly. Initially, we succeeded in producing a large amount with high purity of the His-tagged CyaA-RTX fragment and in establishing the interaction of acylated CyaA-Hly with sheep red blood cell (sRBC) membranes by immuno-localization. Following pre-incubation of sRBCs with non-acylated CyaA-Hly or with the CyaA-RTX fragment that itself produces no hemolytic activity, there was a dramatic decrease in CyaA-Hly-induced hemolysis. When CyaA-RTX was pre-incubated with anti-CyaA-RTX antisera, the capability of CyaA-RTX to neutralize the hemolytic activity of CyaA-Hly was greatly decreased. A homology-based model of the 100-kDa CyaA-RTX subdomain revealed a loop structure in Linker II sharing sequence similarity to human WW domains. Sequence alignment of Linker II with the human WW-domain family revealed highly conserved aromatic residues important for protein-protein interactions. Altogether, our present study demonstrates that the recombinant CyaA-RTX subdomain retains its functionality with respect to binding to target erythrocyte membranes and the WW-homologous region in Linker II conceivably serves as a functional segment required for receptor-binding activity.